2007
DOI: 10.1111/j.1440-1681.2007.04599.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Isosteviol Against Myocardium Injury Induced by Ischaemia–reperfusion in the Isolated Guinea Pig Heart

Abstract: 1. This study aimed to investigate the protective effects of isosteviol against myocardial ischaemia-reperfusion (IR) injury and its effects on mitochondrial adenosine triphosphate (ATP)-sensitive potassium channel (mitoK(ATP)) activity in vitro. 2. Groups of eight guinea pigs were treated as follows: constant perfusion control (PC), IR control, ischaemic preconditioning (IPC) + IR, isosteviol (50, 250 or 500 nmol) + IR, 5-hydroxydecanoate acid (5-HD) (5 micromol) + isosteviol (500 nmol) + IR. The guinea pig h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…1) is an acid hydrolysate of stevioside. We have reported that isosteviol can alleviate the injury induced by ischemia-reperfusion in isolated perfused guinea pig heart (Xu et al, 2007b), rat heart in vivo (Xu et al, 2007a) and rat brain in vivo (Xu et al, 2008). We also found that isosteviol was able to reduce plasma glucose concentrations but did not have an impact on plasma insulin levels during an intravenous glucose tolerance test in Zucker diabetic fatty rats (Ma et al, 2007).…”
Section: Introductionmentioning
confidence: 71%
“…1) is an acid hydrolysate of stevioside. We have reported that isosteviol can alleviate the injury induced by ischemia-reperfusion in isolated perfused guinea pig heart (Xu et al, 2007b), rat heart in vivo (Xu et al, 2007a) and rat brain in vivo (Xu et al, 2008). We also found that isosteviol was able to reduce plasma glucose concentrations but did not have an impact on plasma insulin levels during an intravenous glucose tolerance test in Zucker diabetic fatty rats (Ma et al, 2007).…”
Section: Introductionmentioning
confidence: 71%
“…This cardioprotective effect of isosteviol was similar to that of ischemia preconditioning, and was partly antagonized by a mitoK ATP channel blocker, 5-HD, suggesting that isosteviol may act as a mitoK ATP opener, to exert the protective effect (Miura et al, 2001;Xu et al, 2004). However, this effect has not been confirmed in in vivo animal models.…”
Section: Introductionmentioning
confidence: 91%
“…Studies indicated that both stevioside and isosteviol may possess a variety of biological activities including anti-hypertension, anti-hyperglycemia, anti-inflammatory and potential antitumor effects [18][19][20][21][22]. The myocardium protective effects of isosteviol against ischemia-reperfusion (IR) injury have also been reported [23,24]. Isosteviol is proposed to be able to reduce the infraction area and restore the contractility in cardiac IR in vivo and in isolated hearts without introducing or even improving arrhythmia.…”
Section: Introductionmentioning
confidence: 99%